Waterproof moisture-permeable film

KR103029837B1Active Publication Date: 2026-10-13W SCOPE KOREA CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240024115
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2026-10-13
Estimated Expiration
2044-02-20

Smart Images

  • Figure 112024019457983-PAT00001
    Figure 112024019457983-PAT00001
  • Figure 112024019457983-PAT00002
    Figure 112024019457983-PAT00002
  • Figure 112024019457983-PAT00003
    Figure 112024019457983-PAT00003
Patent Text Reader

Abstract

One aspect of the present invention provides a moisture-permeable waterproof film comprising a porous film having a hydrophobic region comprising a polyolefin; and a hydrophilic region comprising a hydrophilic polymer and a hydrophilic inorganic material dispersed in the hydrophobic region, wherein the content of the hydrophilic polymer in the porous film is 0.1 to 30 weight%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a breathable waterproof film, and more specifically, to a breathable waterproof film capable of mitigating the trade-off between breathability, waterproofness, durability, and mechanical properties to achieve and improve them in a balanced manner. Background Technology

[0002] Clothing, shoes, gloves, hats, etc., often include a layer possessing both breathability and waterproofing properties—so-called a breathable waterproof layer. This breathable waterproof layer can provide a comfortable wearing experience by keeping the wearer dry in humid conditions. Specifically, the breathable waterproof layer allows water vapor, such as sweat, inside the garment to pass through and be released to the outside, while preventing external moisture from penetrating into the garment. By keeping the garment waterproof from rain or snow and allowing sweat to escape, it helps regulate the wearer's body temperature and maintains comfort. With the recent increase in interest in health and leisure activities, fabrics incorporating breathable waterproof layers are being applied in various fields.

[0003] Electrospun nanofiber webs used as breathable waterproof layers have problems such as reduced mechanical properties like strength compared to conventional film-type fabrics, as well as low durability, including easy peeling or scratching, because the nanofibers are not fixed. In response to this, breathable waterproof fabrics in which a fabric coated with a liquid adhesive and a nanofiber web are heat-pressed are known; however, the liquid adhesive reduces and / or closes the pores of the fabric and the nanofiber web, thereby reducing breathability, and the uneven application of the liquid adhesive leads to reduced breathability efficiency. Additionally, attempts have been made to improve scratch resistance and durability by coating the nanofiber web with a hydrophilic polymer such as polyurethane; however, even in this case, the inherent advantages of the nanofiber web, such as breathability, breathability, lightness, softness, and tactile feel, are reduced, and noise is generated or increased during bending and / or friction.

[0004] As a representative breathable waterproof fabric, the breathable waterproof film manufactured using a microporous PTFE membrane and hydrophilic polyurethane is currently GORE-TEX ® It is used in the manufacture of fabric laminates. Although the pore size of the PTFE membrane is larger than a water molecule, the pores are much smaller than individual water droplets; therefore, water vapor can pass through the membrane, whereas water droplets cannot. However, GORE-TEX ® Fluoropolymer resins, the primary raw material for fabrics, are expensive and heavy, and regulations are being tightened due to their harmful effects on the human body and the surrounding environment. In response, a technology has been attempted to impart water repellency to only one side of non-fluorine fabrics, such as polyester, by irradiating them with plasma. However, this plasma treatment increases the material's brittleness, leading to a rapid decline in durability, and reduces breathability, causing discomfort to the wearer. The problem to be solved

[0005] The present invention aims to solve the problems of the aforementioned prior art. The objective of the present invention is to provide a breathable waterproof film capable of balancing and improving breathability, durability, and mechanical properties by mitigating the trade-off between them. means of solving the problem

[0006] One aspect of the present invention provides a moisture-permeable waterproof film comprising a porous film having a hydrophobic region comprising a polyolefin; and a hydrophilic region comprising a hydrophilic polymer and a hydrophilic inorganic material dispersed in the hydrophobic region, wherein the content of the hydrophilic polymer in the porous film is 0.1 to 30 weight%.

[0007] In one embodiment, the content of the hydrophilic inorganic material in the porous film may be 0.1 to 30 weight percent.

[0008] In one embodiment, the content of the hydrophilic region in the porous film may be 0.1 to 60 weight%.

[0009] In one embodiment, the weight-average molecular weight of the polyolefin is 200,000 to 800,000, the content of the hydrophilic polymer in the porous film is 0.1 to 25 weight%, the content of the hydrophilic inorganic material in the porous film is 0.1 to 25 weight%, and the content of the hydrophilic region in the porous film may be 0.2 to 45 weight%.

[0010] In one embodiment, the weight-average molecular weight of the polyolefin is 900,000 to 2,000,000, the content of the hydrophilic polymer in the porous film is 25 to 30 weight%, the content of the hydrophilic inorganic material in the porous film is 25 to 30 weight%, and the content of the hydrophilic region in the porous film may be 45 to 60 weight%.

[0011] In one embodiment, the polyolefin may include one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, and combinations of two or more of these.

[0012] In one embodiment, the hydrophilic polymer may include one selected from the group consisting of ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl alcohol, polyacrylic acid, polyoxyethylene-polyoxypropylene block copolymer, polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl acetal, polyvinyl butyral, cellulose derivative, polyurethane, polyamide, polyester, glycerol, and combinations of two or more of these.

[0013] In one embodiment, the hydrophilic inorganic material may include one selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, talc, and combinations of two or more of these.

[0014] In one embodiment, the porosity of the porous film may be 60 to 90 volume%.

[0015] In one embodiment, the average pore size of the porous film may be 100 to 200 nm.

[0016] In one embodiment, the rate of change in the longitudinal (MD) length from immediately after the application of a water droplet to the surface of the porous film until 5 minutes have elapsed may be 20 to 50%, and the rate of change in the transverse (TD) length may be 20 to 50%.

[0017] In one embodiment, the water vapor transmittance (MVTR) of the porous film measured according to EN ISO 15496 is 5,000 to 20,000 g / m² 2 It can be / 24hr.

[0018] In one embodiment, the porous film may satisfy at least one of the conditions according to (i) to (iv) below.

[0019] (i) thickness 1–30 µm, (ii) puncture strength 500 gf or more, (iii) longitudinal (MD) tensile strength 1,000–3,000 kgf / cm² 2 , (iv) Transverse (TD) tensile strength 1,000~3,000 kgf / cm 2 .

[0020] Another aspect of the present invention provides a laminate article comprising: the breathable waterproof film; and at least one layer bonded in contact with the breathable waterproof film.

[0021] In one embodiment, the layer may include one selected from the group consisting of a textile layer, a polymer film layer, a natural leather layer, a synthetic leather layer, a fleece layer, and a combination of two or more of these. Effects of the invention

[0022] A moisture-permeable waterproof film according to one aspect of the present invention comprises a porous film having a hydrophobic region comprising a polyolefin; and a hydrophilic region comprising a hydrophilic polymer and a hydrophilic inorganic material dispersed in the hydrophobic region. By controlling the content of the hydrophilic polymer, the hydrophilic inorganic material, and the hydrophilic region comprising them, as well as the weight-average molecular weight of the polyolefin, the trade-off between moisture-permeable waterproofness, durability, and mechanical properties in the porous film, the moisture-permeable waterproofness, durability, and mechanical properties can be mitigated and improved in a balanced manner.

[0023] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description or claims of the present invention. Specific details for implementing the invention

[0024] The present invention will be described below. However, the present invention can be implemented in various different forms and is therefore not limited to the embodiments described herein.

[0025] Throughout the specification, when it is stated that a part is "connected" to another part, this includes not only cases where they are "directly connected," but also cases where they are "indirectly connected" with other members interposed between them. Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but rather allows for the inclusion of additional components.

[0026] One aspect of the present invention provides a moisture-permeable waterproof film comprising a porous film having a hydrophobic region comprising a polyolefin; and a hydrophilic region comprising a hydrophilic polymer and a hydrophilic inorganic material dispersed in the hydrophobic region, wherein the content of the hydrophilic polymer in the porous film is 0.1 to 30 weight%.

[0027] In the porous film, the hydrophobic region and the hydrophilic region can each form a continuous phase and a discontinuous phase. Since the hydrophobic region has high surface tension when in contact with moisture, it can lower the wettability of the film to moisture, thereby providing the film with a required level of water resistance. The hydrophilic region can be uniformly dispersed within a matrix composed of the hydrophobic region to provide substantially uniform hydrophilicity to the entire area along the surface area and / or thickness direction of the porous film, and accordingly, contribute to securing the affinity of the porous film to moisture and the resulting moisture permeability.

[0028] Among the hydrophilic regions, the hydrophilic polymer has low surface tension when in contact with moisture, so it can contribute to increasing the wettability of the film to moisture and imparting moisture permeability to the film. The hydrophilic inorganic material also has affinity for moisture and, accordingly, has hygroscopic and / or absorbent properties that absorb moisture present around the porous film to induce or maintain a dry state, so together with the hydrophilic polymer, it can contribute to increasing the wettability of the film to moisture and imparting moisture permeability to the film.

[0029] The term "matrix" as used in this specification refers to a component that constitutes a continuous phase in a film comprising two or more components. That is, in the porous film, the hydrophobic region containing the polyolefin exists as a continuous phase, and the hydrophobic region containing the hydrophilic polymer may exist as a discontinuous phase dispersed therein.

[0030] The content of the hydrophilic polymer in the above porous film may be 0.1 to 30 weight percent. If the content of the hydrophilic polymer is 0.1 weight percent, the required level of hydrophilicity and the resulting moisture permeability cannot be achieved, and if it exceeds 30 weight percent, while hydrophilicity and moisture permeability may be further improved, the mechanical properties of the film, particularly tensile strength and puncture strength, which can be achieved through the hydrophobic region containing the polyolefin, may be reduced. In addition, if the content of the hydrophilic polymer exceeds 30 weight percent, the dispersibility of the hydrophilic polymer is reduced, and the number of surface defects having a size of 2 mm or more and a different brightness from the surroundings on the surface of the porous film increases, which may degrade the appearance quality. Furthermore, moisture permeability, water resistance, and mechanical properties may change rapidly in areas and / or regions where the hydrophilic polymer is randomly aggregated on the surface and / or inside the porous film, which may reduce the reproducibility and reliability of the film.

[0031] The above hydrophilic polymer may include, for example, one selected from the group consisting of ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl alcohol, polyacrylic acid, polyoxyethylene-polyoxypropylene block copolymer, polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl acetal, polyvinyl butyral, cellulose derivative, polyurethane, polyamide, polyester, glycerol, and combinations of two or more of these, preferably may include ethylene vinyl acetate, and more preferably may include ethylene vinyl acetate having a vinyl acetate content of 15 to 30 weight%, but is not limited thereto. If the vinyl acetate content in the ethylene vinyl acetate is less than 15 weight%, the mechanical properties and hydrophilicity of the film may be reduced, and if it exceeds 30 weight%, processability and the dispersibility of the hydrophilic polymer accordingly may be reduced. Meanwhile, as the above-mentioned hydrophilic polymer, in addition to those mentioned above, various types of hydrophilic polymers having hydrophilic functional groups such as amine groups, amide groups, hydroxyl groups, carboxylic acid groups, etc., in the main chain and / or side chain may also be applied.

[0032] The content of the hydrophilic inorganic material in the above porous film may be 0.1 to 30 weight percent. If the content of the hydrophilic inorganic material is 0.1 weight percent, the required level of hydrophilicity and the resulting moisture permeability cannot be achieved, and if it exceeds 30 weight percent, while hydrophilicity and moisture permeability may be further improved, the mechanical properties of the film, particularly tensile strength and puncture strength, which can be achieved through the hydrophobic region containing the polyolefin, may be reduced. In addition, if the content of the hydrophilic inorganic material exceeds 30 weight percent, the dispersibility of the hydrophilic inorganic material is reduced, and the number of surface defects having a size of 2 mm or more and a different brightness from the surroundings on the surface of the porous film increases, which may degrade the appearance quality. Furthermore, moisture permeability, water resistance, and mechanical properties may change rapidly in areas and / or regions where the hydrophilic inorganic material is randomly aggregated on the surface and / or inside the porous film, which may reduce the reproducibility and reliability of the film.

[0033] The above hydrophilic inorganic material may include, for example, one selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, talc, and combinations of two or more of these, preferably may include SiO2, and more preferably may include fumed silica (fumed SiO2), but is not limited thereto. Meanwhile, among the above hydrophilic inorganic materials, in addition to those mentioned above, the surface of the hydrophilic inorganic material, which exists mainly in particulate form, may be modified with a functional group having affinity for the hydrophilic polymer and / or the polyolefin.

[0034] The content of the hydrophilic region, which includes the hydrophilic polymer and the hydrophilic inorganic material in the above porous film, may be 0.1 to 60 weight%. In other words, the total content of the hydrophilic polymer and the hydrophilic inorganic material in the above porous film may be 0.1 to 60 weight%. If the content of the hydrophilic region is 0.1 weight%, the required level of hydrophilicity and the resulting moisture permeability cannot be achieved, and if it exceeds 60 weight%, while hydrophilicity and moisture permeability can be further improved, there is a problem in that the mechanical properties of the film, particularly tensile strength and puncture strength, which can be achieved through the hydrophobic region containing the polyolefin, are reduced, and the required level of water resistance cannot be achieved. In addition, if the content of the hydrophilic region exceeds 60% by weight, the dispersibility of the hydrophilic region is reduced, and the number of surface defects having a size of 2mm or more and a different brightness from the surroundings on the surface of the porous film increases, which may degrade the appearance quality. Furthermore, in areas and / or regions where the hydrophilic region is randomly aggregated on the surface and / or inside the porous film, the moisture permeability, water resistance, and mechanical properties may change rapidly, which may reduce the reproducibility and reliability of the film.

[0035] The above polyolefin may include one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, and combinations of two or more of these, preferably may include at least one of polyethylene and polypropylene, and more preferably may include polyethylene, but is not limited thereto.

[0036] A conventional porous film composed solely of polyolefin is inherently hydrophobic, but a certain amount of hydrophilic polymer and / or hydrophilic inorganic material can be melted and blended with the polyolefin during the manufacture of the film to impart a certain amount of hydrophilicity to the film. In this case, by deriving and combining the molecular weight of the polyolefin and the content of the hydrophilic polymer and / or hydrophilic inorganic material in the film as variables to optimize the required level of moisture permeability, water resistance, and mechanical properties, it is possible to achieve a balance of productivity in the process for melting and blending the hydrophilic polymer and / or hydrophilic inorganic material with the polyolefin, as well as moisture permeability, water resistance, and mechanical properties of the film.

[0037] First, when the polyolefin comprises high-density polyethylene (HDPE), the weight-average molecular weight of the high-density polyethylene may be 200,000 to 800,000, preferably 250,000 to 600,000, more preferably 300,000 to 600,000, and the content of the hydrophilic polymer in the porous film may be 0.1 to 25 wt%, 1 to 20 wt%, 5 to 20 wt%, or 10 to 20 wt%, and the content of the hydrophilic inorganic material in the porous film may be 0.1 to 25 wt%, 1 to 20 wt%, 5 to 20 wt%, or 10 to 20 wt%, and the content of the hydrophilic region in the porous film may be 0.2 to 45 wt%, 10 to 40 wt%, 20 to 40 wt%, or 20 to 35 wt%. The term "weight-average molecular weight" as used in this specification may refer to a value measured by gel permeation chromatography (GPC) using polystyrene as a standard sample according to the method described in the literature (Macromolecules, Vol. 34, No. 19, pp. 6812-6820 (2001) et al.).

[0038] If the content of the hydrophilic polymer in the porous film is less than 0.1% by weight, the required level of hydrophilicity and the resulting moisture permeability cannot be achieved, and if it exceeds 25% by weight, the content of the high-density polyethylene is relatively reduced, and the mechanical properties of the film that can be achieved through the hydrophobic region, in particular, tensile strength and puncture strength, may be reduced. If the content of the hydrophilic inorganic material in the porous film is less than 0.1% by weight, the required level of hydrophilicity and the resulting moisture permeability cannot be achieved, and if it exceeds 25% by weight, the content of the high-density polyethylene is relatively reduced, and the mechanical properties of the film that can be achieved through the hydrophobic region, in particular, tensile strength and puncture strength, may be reduced. In addition, if the content of the hydrophilic region in the porous film is less than 0.2 weight%, the required level of hydrophilicity and the resulting moisture permeability cannot be achieved, and if it exceeds 45 weight%, the hydrophilicity and moisture permeability can be further improved, whereas the mechanical properties of the film that can be achieved through the hydrophobic region containing the high-density polyethylene, particularly tensile strength and puncture strength, are reduced, and the required level of water resistance cannot be achieved, and the appearance quality may be degraded due to surface defects.

[0039] As such, when the content of the hydrophilic region including the hydrophilic polymer and the hydrophilic inorganic material exceeds the upper limit value, the hydrophilicity and moisture permeability of the film may be further improved, while the mechanical properties and water resistance may be reduced. In this regard, the reduced mechanical properties and water resistance can be effectively compensated for and reinforced by using a mixture of high-density polyethylene (HDPE) and ultra-high molecular weight polyethylene (UHMWPE) as the polyolefin, or by replacing high-density polyethylene (HDPE) with ultra-high molecular weight polyethylene (UHMWPE).

[0040] When the above polyolefin includes ultra-high molecular weight polyethylene, the content of the ultra-high molecular weight polyethylene in the hydrophobic region may be 20 to 100 weight%, preferably 30 to 100 weight%, more preferably 50 to 100 weight%. If the content of the ultra-high molecular weight polyethylene in the hydrophobic region is less than 100 weight%, the remainder of the hydrophobic region may be composed of high-density polyethylene. If the content of the ultra-high molecular weight polyethylene in the hydrophobic region is less than 20 weight%, the mechanical properties and water resistance that are degraded by applying an excessive amount of the hydrophilic polymer and / or the hydrophilic inorganic material cannot be adequately compensated for or reinforced.

[0041] The weight-average molecular weight of the ultra-high molecular weight polyethylene may be 900,000 to 2,000,000, preferably 1,000,000 to 2,000,000, more preferably 1,200,000 to 2,000,000, the content of the hydrophilic polymer in the porous film may be 25 to 30 weight%, the content of the hydrophilic inorganic material in the porous film may be 25 to 30 weight%, and the content of the hydrophilic region in the porous film may be 45 to 60 weight%.

[0042] The porosity of the porous film may be 60 to 90 volume%, preferably 70 to 85 volume%, and more preferably 70 to 80 volume%. If the porosity of the porous film is less than 60 volume%, moisture permeability may be reduced, and if it exceeds 90 volume%, water resistance and mechanical properties, particularly tensile strength and puncture strength, may be reduced. The average pore size of the porous film may be 100 to 200 nm, preferably 110 to 180 nm, and more preferably 120 to 170 nm. If the average pore size of the porous film is less than 100 nm, moisture permeability may be reduced, and if it exceeds 200 nm, water resistance and mechanical properties, particularly tensile strength and puncture strength, may be reduced.

[0043] The rate of change in the longitudinal (MD) length from immediately after the application of a water droplet to the surface of the porous film until 5 minutes have elapsed may be 20 to 50%, preferably 25 to 50%, more preferably 30 to 45%, and the rate of change in the transverse (TD) length may be 20 to 50%, preferably 25 to 50%, more preferably 30 to 45%. When the maximum longitudinal (MD) and transverse (TD) lengths immediately after the application of a water droplet to the surface of the porous film are denoted as MD1 and TD1, and the maximum longitudinal (MD) and transverse (TD) lengths at the point 5 minutes have elapsed therefrom are denoted as MD2 and TD2, the rate of change in length may be calculated by the following Equations 1 and 2.

[0044] <Equation 1>

[0045] Percentage change in length (MD) = (MD2-MD1) / (MD1)*100

[0046] <Equation 2>

[0047] Rate of change in transverse (TD) length (%) = (TD2-TD1) / (TD1)*100

[0048] The ratio of the rate of change in the longitudinal (MD) length to the rate of change in the transverse (TD) length of the above droplet may be 0.9 to 1.0, preferably 0.95 to 1.0. If the ratio of the rate of change in the longitudinal (MD) length to the rate of change in the transverse (TD) length of the above droplet falls outside the above range, moisture permeation through the porous film may occur unevenly depending on the direction.

[0049] The water vapor transmittance (MVTR) of the above porous film, measured according to EN ISO 15496, is 5,000–20,000 g / m² 2 / 24hr, preferably, 8,000~20,000g / m² 2 / 24hr, more preferably, 10,000~20,000g / m² 2 It can be / 24hr.

[0050] The porous film above may satisfy at least one of the conditions according to (i) to (iv) below.

[0051] (i) thickness 1 to 30 µm, preferably 5 to 25 µm, more preferably 10 to 20 µm, (ii) puncture strength 500 gf or more, preferably 500 to 1,000 gf, more preferably 700 to 1,000 gf, (iii) longitudinal (MD) tensile strength 1,000 to 3,000 kgf / cm² 2 , preferably, 1,500~2,500 kgf / cm² 2 , more preferably, 1,500~2,000 kgf / cm² 2 , (iv) Transverse (TD) tensile strength 1,000~3,000 kgf / cm 2 , preferably, 1,500~2,500 kgf / cm² 2 , more preferably, 1,500~2,000 kgf / cm² 2 .

[0052] The above-mentioned breathable waterproof film can be manufactured by a method comprising: (a) a step of feeding a composition comprising a polyolefin, a hydrophilic polymer, a hydrophilic inorganic material, and a pore-forming agent into an extruder and forming a base sheet; and (b) a step of stretching the base sheet and then extracting the pore-forming agent, or stretching the base sheet after extracting the pore-forming agent.

[0053] In step (a) above, a composition comprising 10 to 30 weight% of the polyolefin, 0.1 to 10 weight% of the hydrophilic polymer, 0.1 to 10 weight% of the hydrophilic inorganic material, and the remainder of a pore-forming agent may be fed into an extruder to form a base sheet. The types, physical properties, and effects of the polyolefin, the hydrophilic polymer, and the hydrophilic inorganic material are as described above. The input amounts of the polyolefin, the hydrophilic polymer, and the hydrophilic inorganic material may be adjusted so that the content of the hydrophilic polymer and the hydrophilic inorganic material in the porous film is each 0.1 to 30 weight%, and the total content thereof is 0.1 to 60 weight%.

[0054] The above pore-forming agent may be one selected from the group consisting of paraffin oil, paraffin wax, mineral oil, solid paraffin, soybean oil, rapeseed oil, palm oil, coconut oil, di-2-ethylhexyl phthalate, dibutyl phthalate, diisononyl phthalate, diisodecyl phthalate, bis(2-propylheptyl)phthalate, naphthene oil, and combinations of two or more of these, preferably may be paraffin oil, and more preferably may be paraffin oil having a kinematic viscosity of 50 to 100 cSt at 40°C, but is not limited thereto.

[0055] In step (b) above, a porous film may be obtained by stretching the base sheet and then extracting the pore-forming agent, or by extracting the pore-forming agent from the base sheet and then stretching. The stretching may be performed by known methods such as uniaxial stretching or biaxial stretching (sequential or simultaneous). In the case of sequential biaxial stretching, the stretching ratio may be 4 to 20 times in the transverse direction (MD) and the longitudinal direction (TD), respectively, and the corresponding surface ratio may be 16 to 400 times.

[0056] If necessary, the above method may further include (c) a step of heat-setting the porous film obtained in step (b). Heat-setting involves fixing the film and applying heat to forcibly hold the film that is about to shrink, thereby removing residual stress. While a high heat-setting temperature is advantageous for lowering the shrinkage rate, if the temperature is excessively high, the pores formed by partial melting of the film may close, leading to reduced moisture permeability. It is preferable to select a heat-setting temperature within a range where 10 to 30 weight percent of the crystalline portion of the porous film melts. If the heat-setting temperature is selected within this range, it is possible to prevent the problem of insufficient rearrangement of polyolefin molecules within the porous film resulting in no effect of removing residual stress from the film, and the problem of reduced moisture permeability caused by the closure of pores due to partial melting. For example, the heat-setting temperature may be 120 to 150°C, preferably 130 to 145°C, and the heat-setting time may be 5 seconds to 10 minutes, preferably 10 seconds to 1 minute.

[0057] Meanwhile, a laminate article according to another aspect of the present invention may comprise the above-mentioned breathable waterproof film; and at least one layer bonded in contact with the above-mentioned breathable waterproof film. The layer may comprise one selected from the group consisting of a textile layer, a polymer film layer, a natural leather layer, a synthetic leather layer, a fleece layer, and a combination of two or more of these.

[0058] The above laminate article may be a two-layer laminate comprising a textile layer adhered to at least one surface of the porous film. Additionally, the above laminate article may be a three-layer laminate comprising a first textile layer adhered to one surface of the porous film and a second textile layer adhered to the other surface. Furthermore, other layers may be applied to create a multilayer laminate having four, five, six, or more layers. The textile layer may include woven fabrics, nonwoven fabrics, knits, etc. The textile layer may be natural and / or synthetic, for example, cotton, wool, silk, jute, polyamide, polyester, acrylic, aramid, viscose, rayon, carbon fiber, or a combination thereof, but is not limited thereto. The polymer film layer may be, for example, a polyolefin, a polyester, a polyamide, a polyurethane, a polyvinyl alcohol, a polyvinyl acetate, a fluoropolymer, a polyvinyl halide, a polyvinyl chloride, an epoxy resin, a silicone polymer, or a combination thereof, but is not limited thereto.

[0059] Hereinafter, embodiments of the present invention will be described in detail.

[0060] 1. Among the film Ethylene vinyl acetate content of

[0061] Example 1-1

[0062] 17.3 parts by weight of polyethylene (HDPE, PE1) with a weight-average molecular weight (Mw) of 600,000, 7.5 parts by weight of ethylene vinyl acetate (EVA) with a vinyl acetate content of 28% by weight, 5 parts by weight of fumed silica, 0.2 parts by weight of an antioxidant, and 70 parts by weight of paraffin oil with a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin-screw extruder (inner diameter 58 mm, L / D=56). Under conditions of a screw rotation speed of 40 rpm and 200°C, the mixture was extruded from the twin-screw extruder through a T-die with a width of 300 mm and then passed through a casting roll at a temperature of 40°C to produce a base sheet with a thickness of 800 μm.

[0063] The above base sheet was immersed in a dichloromethane leaching tank at 25°C to extract and remove paraffin oil for 1 minute, and then dried at 50°C for 5 minutes. The above base sheet was stretched 8 times in the longitudinal direction (MD) in a roll stretcher at 110°C and stretched 8 times in the transverse direction (TD) in a tenter stretcher at 125°C to produce a porous film.

[0064] Examples 1-2

[0065] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 18.8 parts by weight and 6 parts by weight, respectively.

[0066] Examples 1-3

[0067] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 19.8 parts by weight and 5 parts by weight, respectively.

[0068] Examples 1-4

[0069] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 21.8 parts by weight and 3 parts by weight, respectively.

[0070] Examples 1-5

[0071] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 23.3 parts by weight and 1.5 parts by weight, respectively.

[0072] Examples 1-6

[0073] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 24.5 parts by weight and 0.3 parts by weight, respectively.

[0074] Examples 1-7

[0075] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 24.71 parts by weight and 0.09 parts by weight, respectively.

[0076] Examples 1-8

[0077] 10.8 parts by weight of polyethylene (HDPE, PE1) with a weight-average molecular weight (Mw) of 600,000, 5 parts by weight of polyethylene (UHMWPE, PE2) with a weight-average molecular weight (Mw) of 2,000,000, 9 parts by weight of ethylene vinyl acetate (EVA) with a vinyl acetate content of 28% by weight, 5 parts by weight of fumed silica, 0.2 parts by weight of an antioxidant, and 70 parts by weight of paraffin oil with a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin extruder (inner diameter 58 mm, L / D=56). A base sheet with a thickness of 800㎛ was manufactured by extruding from the above twin-screw extruder into a T-die with a width of 300mm under conditions of a screw rotation speed of 40rpm and 200℃, and then passing it through a casting roll with a temperature of 40℃.

[0078] The above base sheet was immersed in a dichloromethane leaching tank at 25°C to extract and remove paraffin oil for 1 minute, and then dried at 50°C for 5 minutes. The above base sheet was stretched 8 times in the longitudinal direction (MD) in a roll stretcher at 110°C and stretched 8 times in the transverse direction (TD) in a tenter stretcher at 125°C to produce a porous film.

[0079] Examples 1-9

[0080] A porous film was prepared in the same manner as in Examples 1-8, except that the input amounts of PE1, PE2, and EVA were changed to 5 parts by weight, 10.8 parts by weight, and 9 parts by weight, respectively.

[0081] Examples 1-10

[0082] A porous film was prepared in the same manner as in Examples 1-8 above, except that PE1 was not used and the input amounts of PE2 and EVA were changed to 15.8 parts by weight and 9 parts by weight, respectively.

[0083] Comparative Example 1-1

[0084] A porous film was prepared in the same manner as in Example 1-1 above, except that EVA was not used and the amount of PE1 added was changed to 24.8 parts by weight.

[0085] Comparative Example 1-2

[0086] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 15.8 parts by weight and 9 parts by weight, respectively.

[0087] Comparative Examples 1-3

[0088] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of PE1 and EVA were changed to 14.9 parts by weight and 9.9 parts by weight, respectively.

[0089] 2. Content of fumed silica in the film

[0090] Example 2-1

[0091] A porous film was prepared in the same manner as in Example 1-1, except that the input amounts of EVA and fumed silica were changed to 5 parts by weight and 7.5 parts by weight, respectively.

[0092] Example 2-2

[0093] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 18.8 parts by weight and 6 parts by weight, respectively.

[0094] Examples 2-3

[0095] A porous film was prepared using the same method as in Examples 1-3 above.

[0096] Examples 2-4

[0097] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 21.8 parts by weight and 3 parts by weight, respectively.

[0098] Examples 2-5

[0099] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 23.3 parts by weight and 1.5 parts by weight, respectively.

[0100] Examples 2-6

[0101] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 24.5 parts by weight and 0.3 parts by weight, respectively.

[0102] Examples 2-7

[0103] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 24.71 parts by weight and 0.09 parts by weight, respectively.

[0104] Examples 2-8

[0105] A porous film was prepared in the same manner as in Examples 1-8, except that the input amounts of EVA and fumed silica were changed to 5 parts by weight and 9 parts by weight, respectively.

[0106] Examples 2-9

[0107] A porous film was prepared in the same manner as in Examples 1-9 above, except that the input amounts of EVA and fumed silica were changed to 5 parts by weight and 9 parts by weight, respectively.

[0108] Example 2-10

[0109] A porous film was prepared in the same manner as in Examples 1-10, except that the input amounts of EVA and fumed silica were changed to 5 parts by weight and 9 parts by weight, respectively.

[0110] Comparative Example 2-1

[0111] A porous film was prepared in the same manner as in Example 2-1 above, except that fumed silica was not used and the amount of PE1 added was changed to 24.8 parts by weight.

[0112] Comparative Example 2-2

[0113] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 15.8 parts by weight and 9 parts by weight, respectively.

[0114] Comparative Example 2-3

[0115] A porous film was prepared in the same manner as in Example 2-1, except that the input amounts of PE1 and fumed silica were changed to 14.9 parts by weight and 9.9 parts by weight, respectively.

[0116] 3. Content of ethylene vinyl acetate and fumed silica in the film

[0117] Example 3-1

[0118] 11.8 parts by weight of polyethylene (UHMWPE, PE2) with a weight-average molecular weight (Mw) of 2,000,000, 9 parts by weight of ethylene vinyl acetate (EVA) with a vinyl acetate content of 28% by weight, 9 parts by weight of fumed silica, 0.2 parts by weight of an antioxidant, and 70 parts by weight of paraffin oil with a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin extruder (inner diameter 58 mm, L / D=56). Under conditions of a screw rotation speed of 40 rpm and 200°C, the mixture was extruded from the twin extruder through a T-die with a width of 300 mm and then passed through a casting roll at a temperature of 40°C to produce a base sheet with a thickness of 800 μm.

[0119] The above base sheet was immersed in a dichloromethane leaching tank at 25°C to extract and remove paraffin oil for 1 minute, and then dried at 50°C for 5 minutes. The above base sheet was stretched 8 times in the longitudinal direction (MD) in a roll stretcher at 110°C and stretched 8 times in the transverse direction (TD) in a tenter stretcher at 125°C to produce a porous film.

[0120] Example 3-2

[0121] 10.8 parts by weight of polyethylene (HDPE, PE1) with a weight-average molecular weight (Mw) of 600,000, 7 parts by weight of polyethylene (UHMWPE, PE2) with a weight-average molecular weight (Mw) of 2,000,000, 6 parts by weight of ethylene vinyl acetate (EVA) with a vinyl acetate content of 28% by weight, 6 parts by weight of fumed silica, 0.2 parts by weight of an antioxidant, and 70 parts by weight of paraffin oil with a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin extruder (inner diameter 58 mm, L / D=56). A base sheet with a thickness of 800㎛ was manufactured by extruding from the above twin-screw extruder into a T-die with a width of 300mm under conditions of a screw rotation speed of 40rpm and 200℃, and then passing it through a casting roll with a temperature of 40℃.

[0122] The above base sheet was immersed in a dichloromethane leaching tank at 25°C to extract and remove paraffin oil for 1 minute, and then dried at 50°C for 5 minutes. The above base sheet was stretched 8 times in the longitudinal direction (MD) in a roll stretcher at 110°C and stretched 8 times in the transverse direction (TD) in a tenter stretcher at 125°C to produce a porous film.

[0123] Example 3-3

[0124] A porous film was prepared using the same method as in Examples 1-3 above.

[0125] Comparative Example 3-1

[0126] A porous film was prepared in the same manner as in Example 3-1, except that the input amounts of PE2 and EVA were changed to 8.8 parts by weight and 12 parts by weight, respectively.

[0127] Comparative Example 3-2

[0128] A porous film was prepared in the same manner as in Example 3-1, except that the input amounts of PE2, EVA, and fumed silica were changed to 5.8 parts by weight, 12 parts by weight, and 12 parts by weight, respectively.

[0129] 4. Process change

[0130] Example 4

[0131] 19.8 parts by weight of polyethylene (HDPE, PE1) with a weight-average molecular weight (Mw) of 600,000, 5 parts by weight of ethylene vinyl acetate (EVA) with a vinyl acetate content of 28% by weight, 5 parts by weight of fumed silica, 0.2 parts by weight of an antioxidant, and 70 parts by weight of paraffin oil with a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin extruder (inner diameter 58 mm, L / D=56). Under conditions of a screw rotation speed of 40 rpm and 200°C, the mixture was extruded from the twin extruder through a T-die with a width of 300 mm and then passed through a casting roll at a temperature of 40°C to produce a base sheet with a thickness of 800 μm.

[0132] The above base sheet was stretched eight times in the longitudinal direction (MD) in a roll stretcher at 110°C and twice in the transverse direction (TD) in a tenter stretcher at 125°C, and then immersed in a dichloromethane leaching tank at 25°C to extract and remove paraffin oil for 1 minute. After drying at 50°C for 5 minutes, a porous film was prepared by stretching four times in the transverse direction (TD) in a tenter stretcher at 134°C.

[0133] Comparative Example 4

[0134] A porous film comprising 70 wt% polyethylene with a weight-average molecular weight (Mw) of 3,150,000 and 30 wt% polyethylene with a weight-average molecular weight (Mw) of 500,000, and having a porosity of 64.9 vol%, was laminated onto a polyester fabric using an impermeable polyurethane adhesive applied in a discrete dot pattern using a gravure coating roll so that the polyurethane adhesive covers approximately 35% of the film surface, and then the polyurethane adhesive was cured. This two-layer laminate film was then coated with a hydrophilic polyurethane prepolymer mixture containing a thermosetting agent at a concentration of 17 g / m² 2 A breathable waterproof film was manufactured by crosslinking the polyurethane by gravure coating and passing it through an infrared oven for about 20 seconds.

[0135] Experimental Example

[0136] The thickness, porosity, pore size, hydrophilicity, moisture permeability, water resistance, tensile strength, and puncture strength of the porous films prepared in the above examples and comparative examples were measured by the following methods. Unless otherwise noted regarding temperature, measurements were taken at room temperature (25℃), and the results are shown in Tables 1 to 4 below.

[0137] -Thickness (㎛): The thickness of the porous film specimen was measured using a micro-thickness gauge.

[0138] - Porosity (volume%): According to ASTM F316-03, the porosity of a porous film specimen with a radius of 25 mm was measured using a PMI Capillary Porometer.

[0139] - Pore size (nm): Using MediaCybernetics’ Image-pro plus, pores and solids in the porous film specimens were identified based on brightness. Unidentifiable parts or noise were corrected using a freehand tool. Edges forming the outline of the pores and pore structures observed inside the pores were identified as pores, and the pores and solids were binarized. After binarization, continuous parts were considered as a single pore, and the area value of a single pore was assumed to be the area value of a perfect circle to calculate the pore size (pore diameter). The porous film specimens were subdivided into regions of 2㎛*2㎛, and the average pore size was calculated using the average of the pore sizes measured over 10 regions.

[0140] - Hydrophilicity (%): The hydrophilicity of the porous film specimen was measured by the following method. After 2 μL of purified water was dropped onto the surface of the porous film, the size of the droplet generated immediately (MD 3.28 mm / TD 1.86 mm) and the size of the diffused droplet after 5 minutes were measured along the longitudinal direction (MD) and transverse direction (TD), and the rate of change in droplet size (length) in each direction was calculated.

[0141] - Moisture permeability (MVTR, g / m²) 2 / 24hr): The MVTR of the porous film specimen was measured according to DIN EN ISO 15496.

[0142] - Water resistance: A porous film specimen was clamped and sealed between rubber gaskets of a fixture. Water was sprayed for 3 minutes at a pressure of 0.07 bar (1 psig) onto an area of ​​approximately 10.8 cm (4.25 inches) in diameter on one side of the specimen, and water resistance was evaluated based on whether water was observed on the other side of the specimen (O: no water observed, X: water observed).

[0143] - Tensile strength (kgf / cm²) 2 Using a tensile strength tester, the stress applied until fracture occurred in the machine direction (MD) and transverse direction (TD) was measured on a porous film specimen with dimensions of 20 mm * 200 mm.

[0144] - Perforation strength (gf): Using a perforation strength meter, force was applied with a stick to a porous film specimen of size 100mm*50mm until the sample was pierced, and the force applied was measured.

[0145]

[0146]

[0147]

[0149] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.

[0150] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.

Claims

Claim 1 A porous film comprising: a hydrophobic region containing a polyolefin; and a hydrophilic region containing a hydrophilic polymer and a hydrophilic inorganic material dispersed within the hydrophobic region; wherein the content of the hydrophilic polymer in the porous film is 0.1 to 30 wt%, the content of the hydrophilic inorganic material in the porous film is 0.1 to 30 wt%, the porosity of the porous film is 60 to 90 volume%, and the water vapor permeability (MVTR) of the porous film measured according to EN ISO 15496 is 5,000 to 20,000 g / m² 2 24hr breathable waterproof film. Claim 2 delete Claim 3 A breathable waterproof film according to claim 1, wherein the content of the hydrophilic region in the porous film is 0.1 to 60 weight%. Claim 4 A breathable waterproof film according to claim 3, wherein the weight-average molecular weight of the polyolefin is 200,000 to 800,000, the content of the hydrophilic polymer in the porous film is 0.1 to 25 weight%, the content of the hydrophilic inorganic material in the porous film is 0.1 to 25 weight%, and the content of the hydrophilic region in the porous film is 0.2 to 45 weight%. Claim 5 A breathable waterproof film according to claim 3, wherein the weight-average molecular weight of the polyolefin is 900,000 to 2,000,000, the content of the hydrophilic polymer in the porous film is 25 to 30 weight%, the content of the hydrophilic inorganic material in the porous film is 25 to 30 weight%, and the content of the hydrophilic region in the porous film is 45 to 60 weight%. Claim 6 A breathable waterproof film according to claim 1, wherein the polyolefin comprises one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, and combinations of two or more of these. Claim 7 A breathable waterproof film according to claim 1, wherein the hydrophilic polymer comprises one selected from the group consisting of ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl alcohol, polyacrylic acid, polyoxyethylene-polyoxypropylene block copolymer, polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl acetal, polyvinyl butyral, cellulose derivative, polyurethane, polyamide, polyester, glycerol, and combinations of two or more of these. Claim 8 A breathable waterproof film according to claim 1, wherein the hydrophilic inorganic material comprises one selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, talc, and combinations of two or more of these. Claim 9 delete Claim 10 A breathable waterproof film according to claim 1, wherein the average pore size of the porous film is 100 to 200 nm. Claim 11 A breathable waterproof film according to claim 1, wherein the rate of change in length in the longitudinal direction (MD) is 20-50% and the rate of change in length in the transverse direction (TD) is 20-50% from immediately after the application of a water droplet to the surface of the porous film until 5 minutes have elapsed. Claim 12 delete Claim 13 In claim 1, the porous film is a breathable waterproof film satisfying at least one of the following conditions (i) to (iv): (i) thickness 1 to 30 μm, (ii) puncture strength 500 gf or more, (iii) longitudinal (MD) tensile strength 1,000 to 3,000 kgf / cm² 2 (iv) Transverse (TD) tensile strength 1,000~3,000 kgf / cm² 2 . Claim 14 A laminate article comprising: a breathable waterproof film according to any one of claims 1, 3 to 8, 10, 11 and 13; and at least one layer bonded in contact with the breathable waterproof film. Claim 15 A laminated article according to claim 14, wherein the layer comprises one selected from the group consisting of a textile layer, a polymer film layer, a natural leather layer, a synthetic leather layer, a fleece layer, and a combination of two or more of these.

Citation Information

Patent Citations

  • Moisture-permeable and water-proof fabric for fall-winter wear, and process for producing the same

    KR101296821B1

  • Microporous Breathable Film and Method of Making Microporous Breathable Film

    KR1020180030628A

  • Porous film and process for producing the same

    KR1020010102226A

  • A separator and a method for manufacturing the same

    KR1020230079284A